Tea Plants With Gray Blight Have Altered Root Exudates That Recruit a Beneficial Rhizosphere Microbiome to Prime Immunity Against Aboveground Pathogen Infection - Wang, Qiaomei; Yang, Ruijuan; Peng, Wenshu; Yang, Yanmei; Ma, Xiaoling; Zhang, Wenjie; Ji, Aibing; Liu, Li; Liu, Pei; Yan, Liang; Hu, Xianqi (Frontiers in Microbiology, 2021)
Plants with aboveground pathogen infections can recruit beneficial rhizosphere microbes by altering their root exudates to resist subsequent pathogen infection. Whether such a mechanism is activated in tea plants infected with Pseudopestalotiopsis camelliae-sinensis and suitable for the prevention and control of tea gray blight is unknown. In this study, to verify this mechanism, we prepared conditioned soil by planting tea seedlings and inoculating the leaves of tea seedlings with Ps. camelliae-sinensis and analyzed the rhizosphere microbial communities. Then, we examined the growth performance and disease resistance of fresh tea seedlings grown in conditioned and control soils. Further, we evaluated the effect of altered root exudates on shaping the rhizosphere microbial communities. The results showed that tea seedlings grown in conditioned soil had lower disease index values and higher growth vigor. Soil microbiome analysis revealed that the rhizospheric fungal and bacterial communities were altered upon infection with Ps. camelliae-sinensis. Genus-level analysis showed that the fungi Trichoderma, Penicillium, and Gliocladiopsis and the bacteria Pseudomonas, Streptomyces, Bacillus, and Burkholderia were significantly increased in conditioned soil. Through isolation, culture, and inoculation tests, we found that most isolates from the induced microbial genera showed strong antagonism against Ps. camelliae-sinensis and promoted tea seedling growth. Infected tea seedlings exhibited significantly higher exudate levels of phenolic acids and flavonoids and lower exudate levels of amino acids and organic acids, and exogenously applied phenolic acids and flavonoids suppressed gray blight disease. In summary, our findings suggest that tea plants with gray blight can recruit beneficial rhizosphere microorganisms by altering their root exudates, improving the disease resistance of their offspring growing in the same soil.